PENERAPAN METODE INTERACTIVE DEVELOPMENT DALAM PEMBELAJARAN KETERAMPILAN BERBICARA DI MERCURY EDUCATION CENTRE (MEC) PAMEKASAN - Kristanti Ayuanita (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
The purpose of this study is to know how is the application of Interactive development method in teaching speaking skill in Mercury Education Centre (MEC) Pamekasan, what are the difficulties in applying interactive development method in teaching speaking skill in Mercury Education Centre (MEC) Pamekasan. The researcher uses qualitative approach with descriptive kind of research. The data collection means are observation, interview, field notes and data documentation. To check the validity of the data, the researcher uses the techniques of  longer observation, triangulation. The research result show that the interactive development method started with giving motivation in the beginning and the end of the class. After that the students are given some minutes to pronounce vocabulary and to make sentences to do debate or presentation. While the difficulties faced are the different ability to memorize words, the large amount of the students in a class, the students’ condition, and also the different atmosphere between the school and Mercury. The effort done by the teacher coping these difficulties are giving more motivation, giving reward or appreciation, making the target system arranging to send the mentor to go on seminar on it.